Iodine status of pregnant women in Iceland: A cross-sectional study of women from 11-14 weeks gestation - Sólveig Anna Aðalsteinsdóttir 1994- (2019)
Introduction: Iodine is an essential constituent of thyroid hormone, thus plays a key role in numerous developmental and metabolic processes. Adequate iodine consumption during pregnancy is pivotal to ensure proper growth of the developing fetus. Iceland has historically been considered an iodine sufficient nation due to high fish and dairy consumption, however, changes in dietary habits may be contributing to an arising public health issue. Objective: To reassess the iodine status of the population of pregnant women in Iceland and determine those most at risk for deficiency. Methods: Cross-sectional study of women attending their first sonar appointment in gestational weeks 11-14 at National University Hospital in the period from October 2017 – March 2018. Spot urine samples were collected to determine urinary iodine concentration (UIC) and the ratio of iodine to creatinine (I:Cr) was calculated. Results on UIC were compared with the optimal range defined by WHO (median UIC of 150-249 μg/L in pregnancy and not more than 20% of the population below 50 g/L). The results are presented as median UIC (mUIC) with 95% confidence interval (95% CI). A food frequency questionnaire (FFQ) was completed to assess dietary consumption of the main sources of iodine in the Icelandic diet (dairy and fish), and evaluated the percent of women following dietary guidelines for fish and dairy consumption (fish ≥2 times/week, dairy products ≥2 portions/day). Results: Of the 1,350 women eligible to participate in the presents study,1,015 signed informed consent forms (75%).Urine samples collected from 983 participants (73%). The median UIC was 89 (42-141) μg/L and 30% of the sample population had UIC below 50 μg/L. Only 35% of women reported following dietary recommendations for fish, 19% followed recommendations for dairy, and 7.5% followed both. Those who avoided dairy products (n=40) had mUIC of 65 (11-85) μg/L compared to mUIC of 91 (38-158) μg/L of the group that did not avoid dairy products (p=.01). The group of women who ...